Fatores ergonômicos na saúde dos associados da ACEMPRE para contribuição Desenvolvimento Rural Sustentável - Martins, Ivan Maurício (2023)
Population with and the growing demand for food have highlighted family farming as an important segment to meet these needs. However, health promotion is one of the great challenges of public health. In context, a case study way carried out with the analysis of 20 rural producers from ACEMPRE in Marechal Cândido Rondon – PR to evaluate quality of life and the ergonomic contribution to the promotion of the health of these works. The results show that most rural producers work with vegetable production and that the average age and rural work, the average age was 52 years and activity time of 28 years. Risks that can lead to injuries, such as heavy lifting, carrying water and firewood, in addition to inappropriate postures during work. According to a study, rural workers have a high rate of pain and skeletal disorders due to the lack of ergomonic principles, which is crucial to provide a better quality of life for these workers,through health promotion and improvement of public policies.